« Tout le monde peut pas se permettre d’être une hippie comme moi » - Anouck Manez (La Nouvelle Revue du Travail)
The article focuses on a highly stigmatised category of joblessness where individuals are often referred to as being “voluntarily unemployed”. Interviewees here - all of whom stated they were “not actively seeking work” – had certain attributes in common, including biographical availability, far-left commitments or values and shared narratives regarding the negative wage labour situations they had experienced. On the other hand, they differed strongly in terms of the socioeconomic classes to which each belonged and as regards each individual’s actual distance from paid employment. For instance, the best-educated interviewees i.e. those with the greatest economic capital, could “afford” to pursue a highly precarious lifestyle and formulate a narrative entailing a radical rejection of all productive activities. Things were very different for respondents coming from less affluent social classes, who had been socialised to have a strong work ethic while also being constrained by economic necessity and the way their declining employability made it harder for them to find a stable job.